STIMULUS AND RESPONSE INTERFERENCE: BEHAVIOUR AND NEUROPHYSIOLOGY OF THE FLANKER EFFECT - Di Chiaro, Nunzia Valentina (2023)
Constantly, we are influenced by irrelevant information which is fundamental to ignore to result in effective behaviours. In this research project, we used a colour version of the Flanker task to study interference control - the ability to overcome the influence of irrelevant stimuli and competing responses. In Chapter 1, we will present the dual process model used to understand cognitive processes involved in conflict situations. In the Flanker task, the indirect route (controlled) drives the activation of the correct response, whereas the direct route (automatic) activates the incorrect response triggered by flankers. The brain needs to resolve the conflict between the two competing responses before choosing the appropriate one, resulting in slower and less accurate performance. Some previous studies showed that interference effects may differ depending on a person’s age, however the literature is still controversial. In our behavioural experiment, presented in Chapter 2, we investigated the lifespan development of stimulus and response interference in children, and in young and older adults. We found that performance at all ages was significantly influenced by competing stimuli and responses. Most importantly, the size of interference effects decreased with age. In the literature, electromyographic (EMG) studies have underlined the importance to investigate, across time, motor processes in both hands. In our experiment (Chapter 3), we used dynamometers and EMG to investigate the motor processes in both responding (chosen) and non-responding (unchosen) hands, continuously across time. As expected, we found activation of the chosen hand. This activation was preceded (~150 ms) by a deactivation of the unchosen hand. These hand motor processes did not differ between the flanker interference conditions. In the next experiment (Chapter 4), we used transcranial magnetic stimulation (TMS) over the primary motor cortex (M1) to investigate corticospinal excitability related to chosen and unchosen hands. We were interested in motor processes occurring before the reaction time (RT). In the chosen hand, motor-evoked potential (MEP) amplitudes started increasing 156 ms before the RT. This process did not differ across flanker interference conditions. In the unchosen hand, MEP amplitude was not different from baseline. We therefore partially replicated the findings of the EMG experiment. In our last experiment (Chapter 5), we used TMS over the supplementary motor area (SMA) to study the timing and the role of this brain area in preparation of hand motor responses. Surprisingly, we did not find any effects of TMS on the preparation process of responses. We were cautious in interpreting these results considering the exploratory nature. Taking these findings together, we hypothesise a constructive process between hands rather than a response competition as hypothesised in the dual process model. However, further studies are required aimed to explore the functional and temporal aspects of the motor mechanisms.